When AI Helps Yet Hinders: GenAI’s Dual Effects on SDL and CT - Anis Fitriah (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
This study examines the dual impact of Generative Artificial Intelligence (GenAI), specifically ChatGPT, on Self-Regulated Learning (SDL) and Critical Thinking (CT) among college students. Using a Rapid Literature Review method, the study synthesized peer-reviewed articles published between 2020 and 2025. Data were analyzed through thematic narrative synthesis to identify consistent patterns across the findings. The results indicate that GenAI significantly enhances SDL by facilitating task planning, reducing initial cognitive load, enhancing motivation, and increasing students' sense of competence and autonomy. However, the findings also reveal a paradoxical effect: over-reliance on AI encourages cognitive displacement, reduces deep engagement with learning tasks, and weakens core CT capabilities, particularly analysis, evaluation, and reflective judgment. The study identifies four mediating factors Generative AI Literacy (GAIL), AI dependency, information literacy, and instructional scaffolding that determine whether GenAI is a catalyst or a barrier to cognitive development. The novelty of this review lies in its emphasis on the autonomy-dependency paradox in AI-based learning. This study implies that higher education institutions should integrate AI literacy and reflective learning design to maximize benefits while preventing the erosion of AI-based learning